The Impact of the Use of Microsoft Mathematics Calculus Visualization on Student’s Attitude - Rabi, Fazli; Fengqi, Ma; Aziz, Muhammad (American Journal of Creative Education, 2022)
The application of mathematical concepts to real-world problems causes students to have difficulty with the concepts. On undergraduate students, a quasi-experimental research study and visualisation of calculus concepts were conducted as part of a larger project. They were discovered to have a preference for mathematics. As a result, students gained a better understanding of concepts and a more positive attitude. In our class, we had two groups of students who were both from the computer science department and who had both taken the same calculus course. Each group, consisting of fifteen students, was divided into two groups: the control group and the experimental group. Using a traditional learning method, the students in the control group were taught topics such as differentiation and integration, among others. The experiment group, on the other hand, had taught the same lesson using a Microsoft Mathematics visualisation tool, instead. The findings revealed that using Microsoft Mathematics visualisation, the students gained a more significant, positive, broader, and conceptual understanding of calculus than they would have otherwise. In addition, the quasi-experimental study found that there was a statistically significant difference in students’ attitudes between the pre-test and the post-test. With the help of Microsoft Mathematics visualisation, students were more fascinated and attracted towards calculus concepts than before.